Composite catalyst for preparing polylactic acid by ring-opening polymerization of lactide and preparation method thereof
The composite catalyst prepared by manganese dioxide and cobalt trioxide solves the metal tin residue and biotoxicity problems of existing catalysts in the lactide ring-opening polymerization, and achieves efficient and stable high-molecular weight polylactic acid synthesis and catalysts Recycling reduces production costs.
Patent Information
- Application Number
- CN202310261486.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-03-17
AI Technical Summary
Existing lactide ring-opening polymerization catalysts such as stannous octoate catalytic systems have problems with metal tin residues and biotoxicity, which leads to high production costs and difficulty in recycling of polylactic acid, and the effect of cheap metal oxide catalysts is limited.
The composite catalyst is prepared by mixing manganese dioxide and cobalt trioxide in a specific proportion. The stable catalyst is obtained through a three-stage program of heating and calcination, and is used in the ring-opening polymerization of lactide, combined with nitrogen protection and segmented heating reaction technology to prepare High molecular weight polylactic acid.
The efficient catalytic production of high molecular weight polylactic acid is achieved, avoiding metal tin residues, and the catalyst is stable and recyclable, reducing production costs, and meeting the requirements of commercial optical purity.
Smart Images

Figure CN116333287B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite catalyst for preparing polylactic acid through ring-opening polymerization of lactide and a preparation method thereof, belonging to the technical field of polylactic acid synthesis. Background Art
[0002] Polylactic acid (PLA) is a chemically synthesized fully biodegradable material. It not only has good biodegradability, but also has good biocompatibility and mechanical and physical properties. It has broad application prospects in human tissue repair, wound suturing, controlled release of medicines and pesticides. At the same time, polylactic acid is suitable for blow molding, thermoforming and other methods. It is easy to process and has a wide source of synthetic raw materials. It is expected to replace some materials such as polyvinyl chloride, polypropylene, and polystyrene for the production of plastic products, and has received widespread attention at home and abroad. There are two main methods for synthesizing polylactic acid. One method is to generate polylactic acid by dehydration polymerization of lactic acid. The molecular weight of the polylactic acid synthesized by this method is not high, which limits the application of polylactic acid. The other method is to generate polylactic acid by ring-opening polymerization of the intermediate lactide. This method can obtain high molecular weight polylactic acid.
[0003] At present, stannous octoate is the most commonly used catalyst for obtaining polylactic acid by ring-opening polymerization of lactide. Although good results can be obtained, because the tin catalytic system is homogeneous, Sn (II) cannot be recovered, and metallic tin residues will inevitably be produced. The biological toxicity of Sn (II) greatly limits the use of polylactic acid produced by this approach. In order to remove the residual metallic tin, it is often necessary to go through a more complicated post-processing process, and the catalyst cannot be recycled, which greatly increases the cost of producing polylactic acid, so the development of new catalysts is still a key technical problem in the production of polylactic acid. Cheap and easy-to-operate catalysts are particularly important for the catalytic research of ring-opening polymerization of lactide. Although there are many reports on metal coordination, reports using cheap metal oxides are uncommon. In 2021, Chakraborty et al. used cheap cobalt oxides as catalysts for ROP of lactide. The reaction produced polylactic acid at 140°C, but its molecular weight was not high and the catalytic effect was very limited (Mandal, M.; Chakraborty, DJ Polym. Res. 2021, 28, 52.). Summary of the invention
[0004] The purpose of the present invention is to provide a composite catalyst for preparing polylactic acid by ring-opening polymerization of lactide and a preparation method thereof. The catalyst is suitable for synthesizing high molecular weight polylactic acid.
[0005] The technical solution for achieving the purpose of the present invention is as follows:
[0006] The method for preparing a composite catalyst for preparing polylactic acid by ring-opening polymerization of lactide comprises the following steps:
[0007] Manganese dioxide and cobalt trioxide are uniformly mixed in a mass ratio of 6:4 to 7:3, placed in a tubular furnace, introduced with nitrogen, and set a three-stage temperature increase program: first increase the temperature to 140°C to 170°C and keep the temperature constant for 0.5h to 1.5h; then increase the temperature to 330°C to 360°C and keep the temperature constant for 0.5h to 1.5h; finally increase the temperature to 520°C to 570°C and keep the temperature constant for 5h to 8h. After the calcination is completed, cool to room temperature to obtain a composite catalyst.
[0008] Preferably, the mass ratio of manganese dioxide to cobalt trioxide is 6:4, and the composite catalyst prepared under this ratio has the best catalytic effect.
[0009] Preferably, the nitrogen flow rate is 100 ml / min.
[0010] Preferably, the heating rate is 2 to 5°C / min.
[0011] Preferably, three stages of programmed temperature increase are set: first increase the temperature to 150°C at 5°C / min and keep the temperature constant for 1 hour; then increase the temperature to 350°C at 5°C / min and keep the temperature constant for 1 hour; finally increase the temperature to 550°C at 5°C / min and keep the temperature constant for 6 hours. The composite catalyst prepared under the programmed temperature increase has the highest catalytic activity and the synthesized polylactic acid has the largest molecular weight.
[0012] The invention also provides a composite catalyst prepared by the preparation method.
[0013] Furthermore, the present invention provides the use of the composite catalyst in preparing polylactic acid by ring-opening polymerization of lactide.
[0014] Specifically, the application method is: L-lactide, erythrobutene tetraol and a composite catalyst are mixed, and a polymerization reaction is carried out under nitrogen protection, the temperature is first raised to 110°C to 125°C, and the reaction is carried out for 0.5h to 1.5h, then the temperature is raised to 130°C to 150°C, and the reaction is carried out for 0.5h to 1.5h, and finally the temperature is raised to 160°C to 185°C, and the reaction is carried out for 3h to 4.5h. After the reaction is completed, the reaction is naturally cooled, and the crude product is purified and dried to obtain polylactic acid.
[0015] Preferably, the purification method is to first dissolve the crude product with chloroform, precipitate with methanol, and filter.
[0016] Preferably, the polymerization reaction procedure is: first heating to 120°C, reacting for 1 hour, then heating to 145°C, reacting for 1 hour, and finally heating to 165°C, reacting for 4 hours. The polylactic acid synthesized under this condition has the largest molecular weight and the highest optical purity.
[0017] Preferably, the mass of the composite catalyst is 0.7% to 0.8% of the mass of L-lactide, more preferably 0.7%. At this amount, the reaction rate is moderate and degradation can be avoided.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] (1) The present invention uses cheap and readily available manganese dioxide and cobalt trioxide as raw materials to prepare a composite catalyst. The composite catalyst has good catalytic activity in the process of lactide ring-opening polymerization, and as an inorganic catalyst, it avoids the biological toxicity of stannous octoate on the one hand, and on the other hand, it has more stable performance and can be recycled for multiple times without deactivation.
[0020] (2) The composite catalyst of the present invention is applied to the ring-opening polymerization reaction of lactide to prepare polylactic acid with a very high molecular weight in a very short polymerization time, and the prepared polylactic acid can basically meet the commercial optical purity requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the electron microscope image of MnO2;
[0022] Figure 2 This is the scanning electron microscope image of Co2O3;
[0023] Figure 3 This is the SEM-EDS image of the MnO2-Co2O3 composite catalyst (the mass ratio of Co2O3 and MnO2 is 7:3);
[0024] Figure 4 XRD patterns of MnO2, Co2O3, and MnO2-Co2O3 composite catalysts;
[0025] Figure 5 This is the Fourier infrared spectrum of MnO2, Co2O3, and MnO2-Co2O3 composite catalyst. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with specific embodiments and accompanying drawings.
[0027] Example 1
[0028] Weigh 1.8g of dry manganese dioxide and 1.2g of cobalt trioxide (the mass ratio of MnO2 and Co2O3 is 6:4), put them into a corundum boat, and mix them evenly. Put the mixture into a tube furnace, set the nitrogen flow rate to 100ml / min, pass nitrogen for 30 minutes, and set the heating program: heat to 150℃ at 5℃ / min, hold for 1h, then heat to 350℃ at 5℃ / min, hold for 1h. Finally, heat to 550℃ at 5℃ / min and hold for 6h. After the reaction is completed, wait for the tube furnace to cool to room temperature, open the tube furnace, and take out the product MnO2-Co2O3 composite catalyst.
[0029] Figure 1This is a scanning electron microscope image of MnO2. From the image, we can see that the surface of MnO2 is rough, the sizes are different, and it is in irregular blocks.
[0030] Figure 2 This is a scanning electron microscope image of Co2O3. Analysis of the image shows that the surface of Co2O3 is relatively smooth, spherical, and the particle size is about 2μm.
[0031] Figure 3 This is the SEM-EDS image of the MnO2-Co2O3 composite catalyst (the mass ratio of Co2O3 and MnO2 is 7:3). From the figure, we can see that the content of Mn and Co is relatively high. From the Mn K and Co K diagrams, we can see that Mn and Co are well dispersed and evenly distributed. The two elements are intertwined, and new chemical bonds may have been generated.
[0032] Figure 4 The XRD diagrams of MnO2, Co2O3, and MnO2-Co2O3 composite catalysts show that the typical characteristic peak of MnO2 appears at 2θ=57° from the XRD diagram of MnO2; the typical characteristic peaks of Co2O3 appear at 2θ=31°, 38°, 52°, 57°, and 67° from the XRD diagram of Co2O3, proving that the two substances are MnO2 and Co2O3. The XRD diagram of the composite catalyst shows that the typical characteristic peaks of Co2O3 appear at 2θ=27°, 31°, 38°, 52°, 57°, and 67°, and the typical characteristic peaks of MnO2 appear at 2θ=36°, 57°, and 67°, proving that the MnO2-Co2O3 composite catalyst (the mass ratio of Co2O3 to MnO2 is 7:3) is well mixed. Comprehensive analysis shows that MnO2 and Co2O3 have no other impurities. The crystallization peaks of the synthesis of the two substances after high-temperature reaction retain some characteristics of MnO2 and Co2O3, but most of the crystallization peaks are shifted, and the peak width increases or decreases. This is because after the high-temperature reaction of the synthesis, the molecular bonds of MnO2 and Co2O3 are recombined and the properties of the material are changed.
[0033] from Figure 5 It can be seen that the infrared absorption peak of the MnO2-Co2O3 composite catalyst (the mass ratio of Co2O3 to MnO2 is 7:3) is quite different from the infrared absorption peaks of MO2 and Co2O3, which is at 572-577cm -1 and 663~666cm -1 The vibration peak of Co-O bond appears (within the error range), while the vibration peak of Mn-O bond does not appear, which may be due to the low proportion of MnO2 and the weak signal-to-noise ratio. -1 、666cm -1 The peak at 2361cm-1 、3855cm -1 The absorption peak at 572 cm -1 、663cm -1 The peaks are mainly due to the breakage and recombination of the molecular bonds of MnO2 and Co2O3.
[0034] Example 2
[0035] (1) Before the reaction, the raw materials (L-lactide, erythrobutylene glycol, and the composite catalyst prepared in Example 1) were placed in a vacuum oven for vacuum drying. In order to eliminate the influence of the hydroxyl-containing substances that may adhere to the polymerization process, the reaction tube (first washed with distilled water and then washed with anhydrous ethanol) was treated in a vacuum drying oven for 2 hours (about 80° C.), and then placed in the vacuum drying oven for cooling and standby use.
[0036] (2) Connect the reaction device, including the nitrogen protection device and the exhaust device.
[0037] (3) 2.5 g L-lactide was placed in an eggplant-shaped bottle, and then 0.0042 g of initiator erythritol, 0.0150 g of the composite catalyst prepared in Example 1 (the mass ratio of MnO2 to Co2O3 was 6:4), and a small magnetic particle were added. Then, vacuum silicone oil was applied and the bottle stopper and the connection between the reaction device were sealed with a sealing film. The eggplant-shaped bottle was fixed on an iron frame and connected to a pumping device.
[0038] (4) Turn on the vacuum pump and nitrogen, and perform three-stage vacuuming on the eggplant-shaped bottle.
[0039] (5) Place the oil bath on the heating table, adjust the position of the eggplant-shaped bottle so that the oil covers the reactants, heat the heating table to 120°C, and set the speed to 120 rpm.
[0040] (6) Carry out polymerization reaction: first heat to 120°C and react for 1 hour; then heat to 145°C and react for 1 hour; finally heat to 175°C and react for 6 hours.
[0041] (7) After the reaction is completed, the mixture is cooled naturally to obtain a white block product, which is dissolved in chloroform, precipitated with methanol, filtered, and vacuum dried at 40° C. for 24 h to obtain a white flocculent fiber solid polylactic acid.
[0042] After calculation, the product yield was 93.7%. The molecular weight was determined by gel chromatography to be Mw22764. The optical rotation of the chloroform solution was measured by a visual polarimeter to be -140.96.
[0043] Example 3
[0044] The ratio of the two components of the MnO2-Co2O3 composite catalyst was explored, and the other reaction conditions and experimental process were the same as those in Example 2. The experimental results are shown in Table 1.
[0045] Table 1 Investigation of the ratio of the two components of the MnO2-Co2O3 composite catalyst
[0046]
[0047]
[0048] From the above results, it can be seen that when the mass ratio of the two components of the MnO2-Co2O3 composite catalyst, Co2O3 and MnO2, is 6:4 and 7:3, the composite catalyst has a better catalytic effect and the molecular weight of the synthesized polylactic acid is higher.
[0049] Example 4
[0050] Optimization of reaction temperature in ring-opening polymerization experiment. Because this polymerization experiment adopts staged polymerization, the first stage: heating from room temperature to 120°C, reacting for 1h; the second stage: heating to 145°C again, reacting for 1h; the main polymerization occurs in the third stage, so only the reaction temperature of the third stage is explored, that is, only the reaction temperature of the third stage is changed, the reaction time is 6h, the amount of composite catalyst (the mass ratio of MnO2 and Co2O3 is 6:4) is 0.6% of the mass of L-lactide, and the other reaction conditions and experimental process are the same as Example 2. The experimental results are shown in Table 2.
[0051] Table 2 Optimization of reaction temperature in ring-opening polymerization experiment
[0052]
[0053] From the above results, it can be seen that when the reaction temperature of the third stage is 165°C and 170°C, the catalytic effect of the composite catalyst is better and the molecular weight of the synthesized polylactic acid is higher (No. 3, 4).
[0054] Example 5
[0055] Optimization of reaction time in ring-opening polymerization experiment. Because this polymerization experiment adopts staged polymerization, the first stage: heating from room temperature to 120°C, reacting for 1h; the second stage: heating to 145°C again, reacting for 1h. The main polymerization occurs in the third stage, so only the reaction time of the third stage is explored, that is, only the reaction time of the third stage is changed, the reaction temperature is 165°C, the amount of composite catalyst (the mass ratio of MnO2 and Co2O3 is 6:4) is 0.6% of the mass of L-lactide, and the other reaction conditions and experimental process are the same as Example 2. The experimental results are shown in Table 3.
[0056] Table 3 Optimization of reaction time in ring-opening polymerization experiment
[0057]
[0058]
[0059] From the above results, it can be seen that when the reaction time of the third stage is 4h or 5h, the catalytic effect of the composite catalyst is better and the molecular weight of the synthesized polylactic acid is higher.
[0060] Example 6
[0061] The ring-opening polymerization experiment optimized the amount of composite catalyst (the mass ratio of MnO2 and Co2O3 was 6:4), that is, only the amount of composite catalyst was changed, and the reaction temperature and reaction time were set as follows: the first stage: heating from room temperature to 120°C, reacting for 1h; the second stage: heating to 145°C, reacting for 1h; the third stage, finally heating to 165°C, reacting for 4h. The rest of the reaction conditions and experimental process were the same as in Example 2. The experimental results are shown in Table 4.
[0062] Table 4 Optimization of the amount of composite catalyst in ring-opening polymerization experiment
[0063]
[0064] It can be seen from the above results that when the addition amount of the composite catalyst is 0.7% and 0.8%, the catalytic effect on the polymerization reaction is better and the molecular weight of the synthesized polylactic acid is higher.
[0065] Example 7
[0066] The catalyst used in Example 2 was replaced by MnO2-Co2O3 composite catalyst (the mass ratio of MnO2 and Co2O3 was 6:4), MnO2, and Co2O3, respectively, and the catalytic effects of the three in the ring-opening polymerization of lactide were compared. The reaction temperature and reaction time were set as follows: the first stage: heating from room temperature to 120°C, reacting for 1h; the second stage: heating to 145°C again, reacting for 1h; the third stage, finally heating to 165°C, reacting for 4h. The catalyst addition amount was 0.7%, and the other reaction conditions and experimental process were the same as in Example 2. The experimental results are shown in Table 5.
[0067] Table 5 Comparison of catalytic effects of three catalysts
[0068]
[0069] From the above results, it can be seen that under the condition of equal mass replacement, the catalytic effect of the MnO2-Co2O3 composite catalyst is better than that of any single component.
[0070] Example 8
[0071] After the reaction of Example 2 was completed, an equal amount of raw materials was added to the reaction apparatus (without adding additional catalyst), and the reaction process of Example 2 was repeated again. After the reaction was completed, the reaction was cycled again. The results of multiple cycle reactions are shown in Table 6.
[0072] Table 6 Test of the effect of composite catalyst circulation
[0073]
[0074] The above results indicate that the composite catalyst system remains stable after being recycled for at least seven times and can be used without separating the catalyst. It can be developed into a continuous synthesis process, thus saving production costs.
[0075] Comparative Example 1
[0076] The preparation process of the composite catalyst was explored, and only the calcination procedure of the composite catalyst in Example 1 was changed, and the other reaction conditions and experimental processes remained unchanged. The calcination process is divided into three types: one is single temperature calcination; the second is two-stage temperature calcination; the third is three-stage temperature calcination. The composite catalyst prepared in Example 1 (the mass ratio of MnO2 and Co2O3 is 6:4) was used in the lactide ring-opening polymerization experiment. The specific reaction conditions and experimental process are the same as in Example 2. Only the catalyst in Example 2 is changed, and the rest remains unchanged. The specific settings are as follows:
[0077] (1) Set the temperature program: increase the temperature to 530°C at 5°C / min and hold for 5 h.
[0078] (2) Set the temperature program: increase the temperature to 550°C at 5°C / min and maintain for 5 h.
[0079] (3) Set the temperature program: increase the temperature to 570°C at 5°C / min and maintain for 5 h.
[0080] (4) Set the temperature program: increase the temperature to 340°C at 5°C / min and hold for 1 h; then increase the temperature to 550°C at 5°C / min and hold for 5 h.
[0081] (5) Set the temperature program: increase the temperature to 350°C at 5°C / min and hold for 1 h; then increase the temperature to 550°C at 5°C / min and hold for 5 h.
[0082] (6) Set the temperature program: increase the temperature to 360°C at 5°C / min and hold for 1 h; then increase the temperature to 550°C at 5°C / min and hold for 5 h.
[0083] (7) Set the temperature program: increase the temperature to 350°C at 5°C / min and hold for 0.5 h; then increase the temperature to 550°C at 5°C / min and hold for 5 h.
[0084] (8) Set the temperature program: increase the temperature to 140°C at 5°C / min and hold for 1 h; then increase the temperature to 350°C at 5°C / min and hold for 1 h; finally increase the temperature to 550°C at 5°C / min and hold for 5 h.
[0085] (9) Set the temperature program: increase the temperature to 150°C at 5°C / min and hold for 1 h; then increase the temperature to 350°C at 5°C / min and hold for 1 h; finally increase the temperature to 550°C at 5°C / min and hold for 5 h.
[0086] (10) Set the temperature program: increase the temperature to 160°C at 5°C / min and hold for 1 h; then increase the temperature to 350°C at 5°C / min and hold for 1 h; finally increase the temperature to 550°C at 5°C / min and hold for 5 h.
[0087] (11) Set the temperature program: increase the temperature to 150°C at 5°C / min and hold for 1 h; then increase the temperature to 350°C at 5°C / min and hold for 1 h; finally increase the temperature to 550°C at 5°C / min and hold for 6 h.
[0088] (12) Set the temperature program: increase the temperature to 150°C at 5°C / min and hold for 1 h; then increase the temperature to 350°C at 5°C / min and hold for 1 h; finally increase the temperature to 550°C at 5°C / min and hold for 7 h.
[0089] The experimental results are shown in Table 7.
[0090] Table 7 Exploration of composite catalyst production process
[0091]
[0092]
[0093] It can be seen from the above results that the three-stage temperature calcination process is better than the two-stage temperature calcination process, and the two-stage temperature calcination process is better than the single temperature calcination process. After gradually adjusting and optimizing the preparation process of the composite catalyst, the best preparation process of the composite catalyst is finally determined as: heating to 150°C at 5°C / min and keeping for 1h; then heating to 350°C at 5°C / min and keeping for 1h; finally heating to 550°C at 5°C / min and keeping for 6h.
[0094] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite catalyst for preparing polylactic acid by ring-opening polymerization of lactide, characterized in that: The following steps are involved: Manganese dioxide and cobalt trioxide are uniformly mixed in a mass ratio of 6:4 to 7:3, placed in a tubular furnace, introduced with nitrogen, and set a three-stage temperature increase program: first increase the temperature to 140°C to 170°C and keep the temperature constant for 0.5h to 1.5h; then increase the temperature to 330°C to 360°C and keep the temperature constant for 0.5h to 1.5h; finally increase the temperature to 520°C to 570°C and keep the temperature constant for 5h to 8h. After the calcination is completed, cool to room temperature to obtain a composite catalyst.
2. The preparation method according to claim 1, characterized in that: The nitrogen flow rate was 100 ml / min.
3. The preparation method according to claim 1, characterized in that: The heating rate is 2-5°C / min.
4. The preparation method according to claim 1, characterized in that: Set up three-stage temperature program: first increase the temperature to 150°C at 5°C / min and keep it constant for 1 hour; then increase the temperature to 350°C at 5°C / min and keep it constant for 1 hour; finally increase the temperature to 550°C at 5°C / min and keep it constant for 6 hours.
5. The composite catalyst obtained according to the preparation method according to any one of claims 1 to 4.
6. Use of the composite catalyst according to claim 5 in preparing polylactic acid by ring-opening polymerization of lactide.
7. The use according to claim 6, characterized in that: The specific application method is: L-lactide, erythrotetraol and a composite catalyst are mixed, and a polymerization reaction is carried out under nitrogen protection, the temperature is first raised to 110°C ~ 125°C, and the reaction is carried out for 0.5h ~ 1.5h, then the temperature is raised to 130°C ~ 150°C, and the reaction is carried out for 0.5h ~ 1.5h, and finally the temperature is raised to 160°C ~ 185°C, and the reaction is carried out for 3h ~ 4.5h. After the reaction is completed, the reaction is naturally cooled, the crude product is purified, and dried to obtain polylactic acid.
8. The use according to claim 6, characterized in that: The purification method is to first dissolve the crude product with chloroform, precipitate with methanol, and filter.
9. The use according to claim 6, characterized in that: The polymerization procedure was as follows: first, the temperature was raised to 120°C, the reaction lasted for 1 hour, then the temperature was raised to 145°C, the reaction lasted for 1 hour, and finally the temperature was raised to 165°C, the reaction lasted for 4 hours.
10. The use according to claim 6, characterized in that: The mass of the composite catalyst is 0.7% to 0.8% of the mass of L-lactide.
